Contemporary spinal oncology treatment paradigms and outcomes for metastatic tumors to the spine: A systematic review of breast, prostate, renal, and lung metastases. (July 2017) - Yao, Amy; Sarkiss, Christopher A.; Ladner, Travis R.; Jenkins, Arthur L.
Highlights: 24 studies of management of spinal metastasis were reviewed of 3457 patients. All studies found that primary cancer type significantly influenced survival. Median survival time highest for primary breast and renal cancers, lowest for prostate and lung cancers. Surgery shown to greatly increase quality of life in patients able to tolerate the procedure. Abstract: Metastatic spinal disease most frequently arises from carcinomas of the breast, lung, prostate, and kidney. Management of spinal metastases (SpM) is controversial in the literature. Recent studies advocate more aggressive surgical resection than older studies which called for radiation therapy alone, challenging previously held beliefs in conservative therapy. A literature search of the PubMed database was performed for spinal oncology outcome studies published in the English language between 2006 and 2016. Data concerning study characteristics, patient demographics, tumor origin and spinal location, treatment paradigm, and median survival were collected. The search retrieved 220 articles, 24 of which were eligible to be included. There were overall 3457 patients. Nine studies of 1723 patients discussed parameters affecting median survival time with comparison of different primary cancers. All studies found that primary cancer significantly predicted survival. Median survival time was highest for primary breast and renal cancers and lowest for prostate and lung cancers, respectively. Multiple spinal metastases, a cervical location of metastasis, and pathologic fracture each had no significant influence on survival. Survival in metastatic spinal tumors is largely driven by primary tumor type, and this should influence palliative management decisions. Surgery has been shown to greatly increase quality of life in patients who can tolerate the procedure, even in those previously treated with radiotherapy. Surgery for SpM can be used as first-line therapy for preservation of function and symptom relief. Future studies of management of SpM are warranted and primary tumor diagnosis should be studied to determine contribution to survival.